Istradefylline to Treat Patients with Parkinson's Disease Experiencing "Off" Episodes: A Comprehensive Review - Amnon A. Berger; Ariel Winnick; Alexandra Welschmeyer; Alicia Kaneb; Kevin Berardino; Elyse M. Cornett; Alan D. Kaye; Omar Viswanath; Ivan Urits (MDPI AG, 2020)
Parkinson's disease (PD) is a common neurodegenerative disorder that leads to significant morbidity and disability. PD is caused by a loss of dopaminergic, cholinergic, serotonergic, and noradrenergic neurons in the central nervous system (CNS), and peripherally; the syndromic parkinsonism symptoms of movement disorder, gait disorder, rigidity and tremor are mostly driven by the loss of these neurons in the basal ganglia. Unfortunately, a significant proportion of patients taking levodopa, the standard of care treatment for PD, will begin to experience a decrease in effectiveness at varying times. These periods, referred to as "off episodes", are characterized by increased symptoms and have a detrimental effect on quality of life and disability. Istradefylline, a novel adenosine A2A receptor antagonist, is indicated as a treatment addition to levodopa/carbidopa in patients experiencing "off episodes". It promotes dopaminergic activity by antagonizing adenosine in the basal ganglia. This review will discuss istradefylline as a treatment for PD patients with off episodes.